Withdrawal exposure with withdrawal regulation training for smoking cessation: a randomized controlled pilot trial. (1st July 2016) - Hendricks, Peter S.; Hall, Sharon M.; Tyus, Leslie R.; Thorne, Christopher B.; Lappan, Sara N.; McMurray, Megan V.; Bailey, William C.; Cropsey, Karen L.; Baker, Timothy B.
Highlights: A novel smoking cessation treatment showed feasibility, acceptability, & efficacy. Results suggest mechanisms of action consistent with its theoretical rationale. Additional study of this innovative treatment paradigm is warranted. Abstract: Introduction: Although withdrawal processes form a key motivational basis for cigarette use, smoking cessation treatments appear to exert only modest effects on withdrawal. One treatment option for further reducing withdrawal severity would be to provide smokers with withdrawal regulation training. The objective of this study was to pilot a smoking cessation intervention comprising withdrawal exposure with withdrawal regulation training. Methods: Adult smokers (N = 80) were randomized to one of two conditions: 1) Withdrawal Exposure with Withdrawal Regulation Training (WT), which included the development and application of individualized withdrawal regulation strategies over four separate sessions that spanned the first four hours of abstinence; 2) or Relaxation Control (RC) training, which controlled for the therapeutic contact of WT. All sessions occurred before the quit date, after which differential treatment was discontinued and all participants received brief counseling, nicotine replacement therapy, and self-help literature. Biochemically-confirmed (CO ≤ 3) seven-day point-prevalence abstinence was assessed at Months 2 and 3 after end-of-treatment. Results: Treatment completion and ratings of credibility and efficacy were high and equivalent across conditions. 22.2% of participants in the WT condition were abstinent at both time points, whereas 0% and 4.2% of participants in the RC condition were abstinent at Months 2 and 3 (Month 3 OR = 6.5 [0.73, 59.19]). In-session withdrawal ratings suggested WT improved regulation of withdrawal symptoms, which were in turn associated with abstinence. Conclusions: This small pilot study suggests that WT promotes abstinence by enhancing withdrawal regulation. Results warrant further investigation of this innovative treatment approach.